The Acculturation Experiences of English Language Learners (ELLs) Within the Classroom Learning Environment in the United States - Pierrevil, Dr. Edner (American Journal of Education and Practice, 2025)
Purpose: This qualitative descriptive phenomenological study aimed to investigate the acculturation experiences of English Language Learners (ELLs) within the classroom learning environment in the United States. The central problem of this study was the acculturation experiences of ELLs within in the classroom environment in the United States. This study aimed to examine the acculturation processes of ELLs in a classroom setting in the United States. Berry’s acculturation theory is the framework for the study. Materials and Methods: Giorgi’s descriptive phenomenology technique was utilized to perform the study’s data analysis. Eight participants were recruited through purposive sampling, which allowed the researcher to reach data saturation. The sample consisted of public primary school teachers located in the southeast region of the United States. The accuracy of the transcripts of the semi-structured interviews was verified using member-checking procedures, where participants used their descriptions of the phenomenon to validate the transcripts. Giorgi’s five-step data processing techniques were implemented afterwards. There were nine constituents that appeared in the data concerning the three research questions in the study. The outcomes of the study confirm that it coincides with other studies as well. Findings: It is evident that culturally responsive teaching, as well as improved teacher training for its practice, must be brought to the fore to support ELL integration. That study only confirms peer mentoring and parental involvement in the enhancing ELLs' academic and social outcomes. Such findings call for policy reforms that focus on inclusive practices and bilingual resources in schools for all students. Unique Contribution to theory, Practice and Policy: The study highlights the challenges English Language Learners (ELLs) face, including language barriers, social isolation, and low academic performance. It recommends teacher training, bilingual resources, peer support, parental involvement, and multicultural education to support ELLs’ integration and success. Digital tools like Duolingo and Google Translate are suggested to enhance language learning and classroom engagement. Collaborative efforts from teachers, schools, and families are essential for effective ELL support.